UV/H2O2, UV/H2O2/SnO2 and Fe/H2O2 based advanced oxidation processes for the degradation of disperse violet 63 in aqueous medium. (27th January 2020) - Bokhari, Tanveer Hussain; Ahmad, Noshaba; Jilani, Muhammad Idrees; Saeed, Muhammad; Usman, Muhammad; Haq, Atta Ul; Rehman, Roeya; Iqbal, Munawar; Nazir, Arif; Javed, Tariq
Abstract: The photodegradation of disperse violet 63 dye was investigated in aqueous solution using UV/H2 O2, UV/H2 O2 /SnO2 and Fenton reagent. The maximum decolorization was achieved in 60 min with 50 mg l −1 of dye concentration. The suitability of each process depends upon dye concentration. The photo degradation is very effective at low dye concentration. The degradation percentage increased by enhancing initial amount of hydrogen peroxide and UV irradiation time. The influence of operational parameters like pH, H2 O2 concentration, catalyst amount and dye concentration were investigated. After 60 min reaction time, the maximum decolorization of disperse violet 63 with UV/H2 O2, UV/H2 O2 /SnO2 and Fe/H2 O2 was 81%, 92.7% and 96.4% respectively. The results indicated that Fenton process had more photocatalytic activity for degradation of disperse violet 63 dye than that of UV/H2 O2 and UV/H2 O2 /SnO2 . After 60 min, the comparative decomposition order was Fe/H2 O2 > UV/H2 O2 /SnO2 > UV/H2 O2. It may be concluded that Fenton process could possibly be used for the remediation of toxic pollutants from textile effluents.